(untitled) (Global Journal of Management and Business Research, 2014)
This research paper attempts to study the portfolio performance evaluation of selected Hybrid growth schemes using Net Asset Values, Return, Beta and Standard Deviation and further used the risk adjusted evaluation methods such as Sharpe, Treynor, and Sortino Ratio. Researchers only emphasized on secondary data sources and selected 12 Mutual Fund schemes of 6 mutual fund institutions and the period of study is kept limited for 5 years i.e. from 2007-08 to2011-2012. To test the significance; F-test and Spearman’s rank correlation were used and found out that there is significant difference between NAV’s of two select categories, There is significant difference between scheme returns and benchmark returns of both Hybrid Equity Oriented (HEO) schemes and Hybrid Debt Oriented (HDO) schemes, there is mismatch between ranks of Risk and return of sample funds and the unique risk was meager. On the whole, the performance of the sample Hybrid funds during the study period was average.